Monetary Policy and Bank Performance: An Empirical Study of BI Rate Transmission in the Indonesian Banking Sector - Simatupang, Apriani; Naibaho, Eduard Ary Binsar (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study investigates the impact of Indonesia’s benchmark interest rate (BI Rate) as a monetary policy instrument on various aspects of bank performance, including profitability (ROA, ROE, NIM), credit risk (NPL, LLR), operational efficiency (BOPO), and capital adequacy (CAR). Using panel data regression on 41 commercial banks from 2014 to 2024, the study applies the Random Effect Model as determined by the Hausman tests. The results show that BI Rate has a significant and positive effect on NIM, supporting the theory that interest margins tend to widen during periods of rising interest rates. Conversely, BI Rate shows a significant and negative effect on NPL, LLR, and BOPO, which may reflect increased prudence and operational efficiency by banks during monetary tightening. No significant effects are found on ROA, ROE, and CAR, suggesting these dimensions are shaped by other structural or managerial factors. This research contributes to the literature by integrating multiple dimensions of financial and risk performance in one empirical model, offering insights for policymakers and bank managers in strategically navigating interest rate fluctuations. Keywords: Rate; Performance; Monetary; ROA; NIM